Self-passivating tungsten alloys of the system W-Cr-Y for high temperature applications. (June 2018) - Calvo, A.; Schlueter, K.; Tejado, E.; Pintsuk, G.; Ordás, N.; Iturriza, I.; Neu, R.; Pastor, J.Y.; García-Rosales, C.
Abstract: Self-passivating tungsten based alloys for the first wall armor of future fusion reactors are expected to provide a major safety advantage compared to pure tungsten in case of a loss-of-coolant accident with simultaneous air ingress, due to the formation of a stable protective scale at high temperatures in presence of oxygen which prevents the formation of volatile and radioactive WO3 . This work analyses the oxidation and thermal shock resistance of W-Cr-Y alloys obtained by mechanical alloying followed by HIPing. Alloys with different Cr and Y contents are produced in fully dense form with nanocrystalline or ultrafine-grained microstructure and a dispersion of Y-rich oxide nanoparticles located mainly at the grain boundaries. Isothermal oxidation experiments confirm an excellent oxidation resistance due to the formation of protective oxide scales at the very surface. These layers mainly consist of Cr2 O3 and mixed Y-W and Cr-W oxides. The superior oxidation resistance of these alloys is confirmed by tests simulating accident-like conditions. The thermal conductivity of these alloys at 600–1000 °C is 2–3 times higher than standard Ni-base superalloys like Inconel-718. The material also exhibits outstanding thermal shock resistance: 1000 pulses of 0.19 GW/m 2 power density and 1 ms duration at 400 °C base temperature resulted in no damage, while an increased power density of 0.38 GW/m 2 resulted in the formation of a crack-network and slight surface roughening. An additional thermal treatment at 1550 °C improves slightly the oxidation resistance and significantly the thermal shock resistance of the alloy. Highlights: Fully dense W-Cr-Y alloys of different compositions produced by MA and HIP Y2 O3 nanoparticles at GB inhibit grain growth and improve strength and toughness W-10Cr-01Y has best oxidation resistance at isothermal and accident-like conditions W-10Cr-0.5Y withstood 1000 pulses of 1 ms and 0.19 GW/m 2 at 400 °C without damage 1000 pulses of 0.38 GW/m 2 result in better performance than W reference material